2009
DOI: 10.1080/09669580802359319
|View full text |Cite
|
Sign up to set email alerts
|

Does more interpretation lead to greater outcomes? An assessment of the impacts of multiple layers of interpretation in a zoo context

Abstract: This study investigates the relationship between level of exposure to interpretive media and the cognition, affect and behaviour of zoo visitors, i.e. what they report knowing, feeling and doing following their interpretive experience at the zoo. . Visitors were surveyed at the exit to a particular zoo experience, a recently-opened lion exhibit that uses an array of static and face-to-face interpretive media to convey messages about the difficulties faced by lions, particularly when they come into contact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 19 publications
7
61
0
2
Order By: Relevance
“…While some research in the USA and Australia has shown that demographics tend to be poor predictors of learning (Falk & Adelman, 2003;Falk & Storksdieck, 2005;Falk, 2006;Weiler & Smith, 2009), in a study of visitors to 30 zoos and aquariums in 19 countries, age, gender, education level were found to significantly predict respondents' knowledge of proenvironmental behaviour . In the USA, Vernon (2009) noted that visitor demographics impacted upon conservation learning outcomes, with women and older visitors being more receptive to conservation learning than other visitors.…”
Section: Demographic Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…While some research in the USA and Australia has shown that demographics tend to be poor predictors of learning (Falk & Adelman, 2003;Falk & Storksdieck, 2005;Falk, 2006;Weiler & Smith, 2009), in a study of visitors to 30 zoos and aquariums in 19 countries, age, gender, education level were found to significantly predict respondents' knowledge of proenvironmental behaviour . In the USA, Vernon (2009) noted that visitor demographics impacted upon conservation learning outcomes, with women and older visitors being more receptive to conservation learning than other visitors.…”
Section: Demographic Variablesmentioning
confidence: 99%
“…For example, Weiler and Smith (2009) found that increasing the number of opportunities for visitors to encounter interpretive media increased their self-reported behavioural, cognitive and affective short term outcomes.…”
Section: Design Of Interpretive Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Betty Weiler (2009) investigates relationships between cognition, affection as well as behavior of tourists visiting zoos and the number of interpretive media they used. The results found that 288 visitors used 1 to 4 different interpretive media and with an increase in the number of interpretation media used, the impact of interpretation on visitors also increased [27]. Studies of interpretation outcomes demonstrated that interpretation impacts on visitors' knowledge gain definitely, but increasing visitors' knowledge is not the ultimate goal of interpretation.…”
Section: B Studies Concerning Outcomes Of Interpretation 1) Researchmentioning
confidence: 99%
“…Although interpretation fostered visitors' awareness and support of management policy, such impacts were only restricted to visitors' on-site behaviors [26]. Betty Weiler (2009) investigates relationships between cognition, affection as well as behavior of tourists visiting zoos and the number of interpretive media they used. The results found that 288 visitors used 1 to 4 different interpretive media and with an increase in the number of interpretation media used, the impact of interpretation on visitors also increased [27].…”
Section: B Studies Concerning Outcomes Of Interpretation 1) Researchmentioning
confidence: 99%